MANAJEMEN PEMBELAJARAN GURU DALAM PENERAPAN KURIKULUM MERDEKA MANDIRI BERBAGI DI SD NEGERI 190 BARRU - Nur Hasnita; Wahira; Hasan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to explore how teacher learning management is carried out in the implementation of the Independent Shared Freedom Curriculum at SD Negeri 190 Barru, the challenges faced by teachers, and the strategies they employ to overcome those challenges. This is a qualitative research study using a descriptive method. Data collection techniques include observation, in-depth interviews with teachers, and documentation. The data were analyzed through data reduction, data presentation, and conclusion drawing. The findings show that teacher learning management at SD Negeri 190 Barru has been implemented fairly well and aligns with the principles of the Independent Curriculum, particularly in granting teachers the autonomy to design learning that suits the characteristics of their students. In the planning stage, teachers have used learning outcomes and teaching modules tailored to students’ needs. In the implementation stage, differentiated learning practices were observed. In the evaluation stage, diagnostic, formative, and summative assessments were carried out adequately by the teachers. However, several challenges remain, including limited resources, the need for in-depth teacher training, classroom management skills, and a lack of collaboration among teachers. To address these challenges, teachers have adopted various strategies such as engaging in self-directed training based on individual needs, enhancing collaboration, integrating technology, and developing available resources. This study recommends the provision of supporting facilities to optimize the implementation of the curriculum.